Comparative Evaluation of Alpha-Fetoprotein Serum inHepatocellular Carcinoma Patients with Non-Viral Etiology - Aprilicia, Gita; Bantas, Krisnawati; Syarif, Syahrizal; Kalista, Kemal Fariz (UI Scholars Hub, 2021)
Introduction. Non-viral etiology of hepatocellular carcinoma (HCC) now needs attention. Hepatocellular carcinoma which was caused by hepatitis B and hepatitis C could be controlled in the national program, while HCC from non-B non-C etiology has become a further concern with the with the increased of metabolic syndrome. Serum alpha-fetoprotein is a tumor marker commonly used for screening for HCC in patients with liver cirrhosis (LC). However, in HCC patients with nonviral etiology, AFP serum tends to be normal. This study aimed to evaluate the performance of AFP serum based in HCC and LC patient with non-viral etiology and to evaluate the factors associated with elevated AFP. Methods. Data HCC from registry at Cipto Mangunkusumo Hospital in the period August 2015 to December 2019 were collected. Patients with liver cirrhosis (LC) were taken as the control group. The etiology of liver disease is determined by viral serological examination. Non-viral etiology was defined as a patient who was anti-HCV negative and HBsAg negative. Differences in AFP levels were evaluated by using the Mann Whitney test. Performance of serum AFP in viral and non-viral etiologies were evaluated by receiver operation character (ROC). The factors associated with an increase in AFP by a threshold of 10 ng/ml were evaluated by multivariate analysis using logistic regression. Results. There were 295 HCC patients and 155 LC patients who were included in this study. Non-viral etiology was found in 16.1% of LC group and 14.9% of HCC group. The median serum AFP in HCC patients was higher than in LC patients, 187.50 ng/ml vs. 4.60 ng/ml, p 5 cm was 2.89 (95% CI: 1.56 - 3.67; p value 0.001). Conclusions. AFP Serum is low in HCC patients with non-viral etiology. The increase of serum AFP above 10 ng/ml is associated with etiology of viral hepatitis and tumor size.